Effect of Flux onto Intermetallic Compound Formation and Growth - Siti Rabiatull Aisha, Idris; Noor, Farihan; Hardinnawirda, Kahar (EDP Sciences, 2016)
In this study, the effect of different composition of no-clean flux onto intermetallic compound (IMC) formation and growth was investigated. The solder joint between Sn 3Ag-0.5Cu solder alloy and printed circuit board (PCB) was made through reflow soldering. They were further aged at 125°C and 150°C for up to 1000 hours. Results showed that fluxes significantly affect the IMC thickness and growth. In addition, during aging, the scallop and columnar morphology of IMC changed to a more planar type for both type of flux during isothermal aging. It was observed that the growth behavior of IMC was closely related to initial soldering condition.